Beyond Dopamine: Glutamate as a Target for Future Antipsychotics. (5th July 2012) - Sendt, Kyra-Verena; Giaroli, Giovanni; Tracy, Derek K.
Abstract : The dopamine hypothesis of schizophrenia remains the primary theoretical framework for the pharmacological treatment of the disorder. Despite various lines of evidence of dopaminergic abnormalities and reasonable efficacy of current antipsychotic medication, a significant proportion of patients show suboptimal treatment responses, poor tolerability, and a subsequent lack of treatment concordance. In recent decades, intriguing evidence for the critical involvement of other neurotransmitter systems in the pathophysiology of schizophrenia has emerged, most notably of dysfunctions within the glutamate pathways. Consequently, the glutamate synapse has arisen as a promising target for urgently needed novel antipsychotic compounds—particularly in regards to debilitating negative and cognitive symptoms poorly controlled by currently available drugs. In this paper, recent findings integrating glutamatergic and dopaminergic abnormalities in schizophrenia and their implications for novel pharmacological targets are discussed. An overview of compounds in various stages of development is given: drugs enhancing NMDA receptor function as well as metabotropic glutamate receptor (mGluR) agonist and positive allosteric modulators (PAMs) are emphasised. Together with other agents more indirectly affecting glutamatergic neurotransmission, their potential future role in the pharmacotherapy of schizophrenia is critically evaluated.